Experiment on Fracturability of Shale Reservoir in Yingxiongling Area, Qinghai Oilfield - Chen, Xiwen; Li, Bin; Yu, Fusheng (Scientific Journal of Technology, 2026)
The Yingxiongling Area of Qinghai Oilfield is rich in shale oil resources; however, there are still gaps in the analysis of reservoir geological characteristics and the fracturability evaluation system in this region. To address this, a fracturability evaluation model was established through systematic experiments on reservoir engineering geological characteristics, with the results as follows: The reservoir in the Upper Member of Ganchaigou Formation is prominently characterized by interbedded sedimentation of calcareous shale and calcitic dolomite, with an average porosity of 5.7%. The pore size is concentrated in the micron-scale range of 0.001~0.1 μm, and micron-scale pores are well-developed. The mineral composition is dominated by dolomite, calcite, and clay minerals, among which the average content of clay minerals reaches 65%, and the average rock mechanical brittleness index is 41.76%. Natural fractures in the reservoir are poorly developed, and the difference in fracture pressure between limestone intervals and shale intervals is 10.78~16.68 MPa, which is unfavorable for vertical fracture propagation. The shale reservoir fracturability model shows that the average fracturability index is 0.34, indicating low fracturability and difficulty in forming a complex fracture network. Based on the fracturability model and geological characteristics, a reservoir reconstruction mode of "three-dimensional horizontal well pattern + zipper-type volume fracturing" is proposed. By adopting the technologies of close spacing fracturing + limited-entry perforation + large-displacement continuous sanding, the complexity of fractures is further improved to achieve net pressure interlayer breakthrough.